A nonlinear Luenberger-like observer for nonlinear singular systems. (December 2017) - Zheng, Gang; Boutat, Driss; Wang, Haoping
Abstract: This paper investigates observer design problem for a large class of nonlinear singular systems with multiple outputs. We first regularize the singular system by injecting the derivative of outputs into the system. Then differential geometric method is applied to transform the regularized system into a simple normal form, for which a Luenberger-like observer is proposed.